Ground motion selection for seismic slope displacement analysis using a generalized intensity measure distribution method - Du, Wenqi (2020)
Selecting ground motions based on the generalized intensity measure distribution (GIMD) approach has many appealing features, but it has not been fully verified in engineering practice. In this paper, several suites of ground motions, which have almost identical distributions of spectral acceleration (SA) ordinates but different distributions of non-SA intensity measures, are selected using the GIMD-based approach for a given earthquake scenario. The selected ground motion suites are used to compute the sliding displacements of various slopes. Comparisons of the resulting displacements demonstrate that selecting ground motions with biased distribution of some intensity measures (ie, Arias intensity) may yield systematic biases (up to 60% for some slope types). Therefore, compared to the ground motions selected based only on the distribution of SA ordinates, the ground motion suite selected by the GIMD-based approach can better represent the various characteristics of earthquake loadings, resulting in generally unbiased estimation in specific engineering applications.